2002
DOI: 10.1139/f02-043
|View full text |Cite
|
Sign up to set email alerts
|

Comparative growth and feeding in zebra and quagga mussels (Dreissena polymorphaandDreissena bugensis): implications for North American lakes

Abstract: In laboratory experiments, quagga mussels (Dreissena bugensis) survived as well as zebra mussels (Dreissena polymorpha) and equaled or exceeded their growth rate (–3 to 242% change in wet mass) when reared at 6 or 23°C and fed natural seston or Chlamydomonas at food levels ranging from 0.05–7.4 µg·L–1 chlorophyll a (chl a). Superior growth of quagga mussels was most pronounced at low food levels. We found no significant differences in per capita clearance rates (CR), functional responses, or feeding behavior b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
127
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(147 citation statements)
references
References 37 publications
16
127
2
Order By: Relevance
“…Zebra mussels are small, sessile organisms, widespread filter feeders, resistant to a broad range of environmental conditions (Claudi and Mackie, 1993) and to different types of pollutants (Bervoets et al, 2005). They can concentrate particulate organic matter and indigestible components from water with a clearance rate ranging between 5 and 400 mL/individual/h (Ackerman, 1999;Baldwin et al, 2002). D. polymorpha have their most suitable habitat in stable riverbeds under high flows, a velocity below 1.2 m/s, and a depth of less than 5 m under regular flows (Sanz-Ronda et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Zebra mussels are small, sessile organisms, widespread filter feeders, resistant to a broad range of environmental conditions (Claudi and Mackie, 1993) and to different types of pollutants (Bervoets et al, 2005). They can concentrate particulate organic matter and indigestible components from water with a clearance rate ranging between 5 and 400 mL/individual/h (Ackerman, 1999;Baldwin et al, 2002). D. polymorpha have their most suitable habitat in stable riverbeds under high flows, a velocity below 1.2 m/s, and a depth of less than 5 m under regular flows (Sanz-Ronda et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, the use of other filtering organisms can be interesting for the improvement of waters quality. In this context, the freshwater bivalve Dreissena polymorpha has some characteristics that would make it suitable for the above mentioned purpose: an enormous filtering capacity, ranging from 5 to 400 mL/ bivalve/h [18,19], a high population density, with more than 700,000 individuals/m 2 [20], and the ability to produce feces and pseudofaeces where many contaminants are adsorbed. In fact, these two D. polymorpha waste products, being settleable [21], could easily remove from the water column the bounded pollutants (as MEs).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a species-specific modulation of stress biomarkers in response to contaminants in D. bugensis and D. polymorpha could be expected as well. D. bugensis was proven to allocate more energy to soft tissue relative to shell length (Roe and MacIsaac, 1997), has higher assimilation efficiency (Baldwin et al, 2002), grows faster (Baldwin et al, 2002;Karatayev et al, 2011;Le et al, 2011), filters at a higher rate (Diggins, 2001;Veltman et al, 2008) and was reported to have a lower respiration rate (Stoeckmann, 2003). Interspecies differences were also found for the accumulation of metals and organic contaminants, in general with higher contaminant burdens in D. polymorpha (Rutzke et al, 2000;Richman and Somers, 2005;Schäfer et al, 2012;Matthews et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Several differences in the physiological attributes of the two species were suggested to support the gradual displacement of D. polymorpha by D. bugensis. D. bugensis was shown to have higher assimilation efficiency (Baldwin et al, 2002), higher filtration rate (Diggins, 2001) and lower respiration rate (Stoeckmann, 2003), which imply higher growth rate. These features are particularly important when food resources are limiting.…”
Section: Introductionmentioning
confidence: 99%